Evaluation of the LDR protocol in a hybrid sensor networks/MANET architecture - Zhuoqun Li; Barria, J.A; Lent, R (IET Seminar on Target Tracking and Data Fusion: Algorithms and Applications, 2008)
Rescue operations are often carried out in hostile environments where no static or centralized infrastructure is available to support communications on the move. In this circumstance, a MANET can be formed by a group of mobile devices to enable peer-to-peer communications. Stringent QoS (e.g. delivering packets with high reliability) requirements may be difficult to fulfill for such operations in a MANET because of the high dynamism of nodal mobility and consequently the uncertainty of network topology. Many routing protocols has been recently proposed to evaluate the stability of links in a MANET based on the time-varying relative positions between nodes and to determine a reliable way for packet delivery. However, these protocols rely on the availability of GPS signal or inter-node range estimates. In this paper we analysis and discuss the performance of the link durability routing (LDR) protocol that is distinguished from conventional methods by the exploitation of a hybrid architecture of sensor networks/MANET for locating mobile nodes and real-time assessment of the durability of links. Our simulation results reveal that, in comparison to two benchmark protocols (e.g. AODV and DSR) under the same networking conditions characterized by a dangerous zone mobility model (DZM), the LDR protocol is able to deliver 19% more packets with the hybrid network architecture that achieves energy savings of up to 3 mj for each received data byte.